Base 3 Numeration System Requiring a Negative Digit - Meiring, Steven (Ohio Journal of School Mathematics, 2021)
An investigation of the minimum number of weights for weighing objects on a two-pan balance leads to two interesting discoveries. The first is that the weights must all be powers of three. The second is that a model to describe the process requires a base three numeration system with a negative digit.